Determinants of Dividend Payout Ratio on IDXHIDIV20 Issuers in Indonesia Stock Exchange - Yusbardini Yusbardini; Kurniati W Andani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze the effect ofreturn on investment, operational cash flow, total assets turnover, debt to equity ratio, and firm size on dividend payout ratio on companies that are listed in the IDXHIDIV20. This study uses quantitative method with descriptive approach. The samples were selected using purposive sampling method and the results consisted of 8 companies from 2016-2020. The data analysis was carried out with Data Panel Regression using EViews 10. The results of this study show that return on investment has a negative and significant effect on dividend payout ratio. Meanwhile operational cash flow, total assets turnover, debt to equity ratio, and firm size didn't have any effect.